Inovasi Manajemen Madrasah Berbasis Pesantren dalam Meningkatkan Pembinaan Santri Di Ma’had Al-Hidayah MAN 3 Banyuwangi - Moh Fathul Ikhsan (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
Educational institutions must be able to keep pace with the times and meet the needs of society, as educational institutions, especially pesantren, serve as a crucial platform for the community to address societal demands. The purpose of this research is, first, to understand the implementation of pesantren-based madrasah management at Ma’had Al-Hidayah MAN 3 Banyuwangi. Second, to understand the guidance of students at Ma’had Al-Hidayah MAN 3 Banyuwangi. This research uses a descriptive qualitative research method. With the research conducted at MAN 3 Banyuwangi Srono. The data collection techniques used in this research are interview methods, observation, and documentation. The data needed by the researcher are primary data, which is data obtained directly from informants, and secondary data, which is data in the form of archives or documents about the research object. Data analysis involves reducing all data from the research object, then presenting it according to the research formulation and drawing conclusions. The results of this study indicate that: (1) The Pesantren-Based Madrasah Management Innovation implemented at Ma’had al-Hidayah MAN 3 Banyuwangi has an impact on the activities of the students at the Ma’had, which are directed towards activities related to education and the pesantren curriculum. And on the other hand, to improve the patterns of skills and knowledge in mentoring the students so that they can enhance their abilities. (2) The guidance provided to the students is given through various methods, namely through approach and motivation, accompanied by three indicators of guidance, namely attendance level, ability, and encouragement.